Pengaruh Kemampuan, Komitmen Dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Pabrik Kelapa Sawit I PT. Abdi Budi Mulia Kabupaten Labuhan Batu Selatan Sumatra Utara - Sehani Sehani; Ferdy Lestyawan (Yayasan Almanar Pujud, 2024)
This research was conducted at PT. Abdi Budi Mulia, South Labuhan Batu Regency, North Sumatra, which operates in the Palm Oil sector. The purpose of this study was to determine whether the ability, commitment and work environment have a partial or simultaneous effect on employee performance at the palm oil mill I of PT. Abdi Budi Mulia. The population of the study was 58 people and the sample used was 58 people. The method of determining the sample in this study used a census sample. The data used were primary data and secondary data. The quantitative descriptive analysis method. The results showed that the ability partially had a positive and significant effect on employee performance at PT Budi Abdi Mulia. Commitment partially had a positive and significant effect on employee performance. The work environment had a partial effect on employee performance. Simultaneously, the variables Ability, commitment and work environment had an effect on employee performance. The amount of contribution of the independent variable to the dependent variable was 84,6%.